Technique for preparation of anaerobic microbes: Rodshaped cellulolytic bacteria - Amlius Thalib; B Haryanto; Kuswandi .; H Hamid; Mulyani . (Jurnal Ilmu Ternak dan Veteriner, 2001)
Preparation of anaerobic-rod cellulolytic bacteria with coating technique has been conducted. Steps of the processes involved were cultivation, coating, evaporation, and drying. Coating agent used was Gum Arabic, and drying techniquesconducted were freeze drying and sun drying. pH of culture media was firstly optimized to obtain the maximal population ofbacteria. Both coated and uncoated preparates were subjected to drying. Morphological and Gram type identifications showed that uncoated preparate dried with freeze drying is not contaminated (ie. all bacteria are rod shape with Gram-negative type) while the one dried with sun drying is not morphologically pure (ie. containing of both rod and coccus shapes with Gram negative and positive). The coated preparates dried by both freeze and sun drying, were not contaminated (ie. all are rods with Gram-negative). The coating and drying processes decreased viability of preparates significantly. However, the decreasing of viability of coated preparate are lower than uncoated preparate (ie. 89 vs. 97%). Total count of bacteria in sun-drying coated preparate are higher (P<0.05) than the uncoated preparate (ie. 3.38 x 1010 vs.  1.97 x 1010 colony/g DM). Activity of sun-drying coated preparate to digest elephant grass and rice straw was higher (P<0.01) than the sun-drying uncoated preparate with the in vitro DMD values were 42.7 vs. 35.5% for elephant grass substrate and 29.3 vs. 24.6% for rice straw substrate. Therefore, it is concluded that coating technique has a positive effects on the preparation of rumen bacteria.   Key words : Anaerobic bacteria, coating, drying